Does Psychological Capital Mediate Between Workplace Violence and Depressive Symptoms Among Doctors and Nurses in Chinese General Hospitals? - Li X (Psychology Research and Behavior Management, 2021)
Xiaomeng Li,1,2 Huazhang Wu1 1Department of Health Service Management, China Medical University, Shenyang, Liaoning, 110122, People’s Republic of China; 2Liaoning Academy of Social Sciences, Shenyang, Liaoning, 110032, People’s Republic of ChinaCorrespondence: Huazhang Wu Tel +86-13694129862Email hzwu@cmu.edu.cnBackground: Depressive symptoms related to workplace violence (WPV) have been studied and are the main causes of lower psychological and physical well-being and work motivation. Our study aims to examine the prevalence of depressive symptoms and to explore whether psychological capital (PsyCap) mediates the effect of WPV on depressive symptoms in doctors and nurses.Methods: Participants were recruited from general hospitals in Liaoning, China in 2018. Out of 1218 participants, 1062 (87.2%) completed self-reported questionnaires. Depressive symptoms, WPV and PsyCap were measured by Epidemiologic Studies Depression Scale (CES-D), Workplace Violence Scale (WVS) and Psychological Capital Questionnaire (PCQ), respectively. The related factors of depressive symptoms were investigated by using hierarchical multiple regression in both doctors and nurses.Results: The mean scores of depressive symptoms were 23.09 ± 8.38 in doctors and 22.33 ± 8.95 in nurses, and there was no significant difference between the scores of these two groups. WPV was positively associated with depressive symptoms (doctors: β=0.349, P< 0.001; nurses: β=0.317, P< 0.001) while PsyCap was negatively associated with depressive symptoms (doctors: β=− 0.101, P< 0.001; nurses: β=− 0.230, P< 0.001). In addition, PsyCap acted as a mediating role between WPV and depressive symptoms in both doctors and nurses.Conclusion: Both doctors and nurses had serious depressive symptoms. WPV could aggravate depressive symptoms, while PsyCap could aggravate against depressive symptoms. When PsyCap acted as a mediator, WPV had a negative impact on PsyCap, which could increase doctors’ and nurses’ depressive symptoms.Keywords: doctors, nurses, workplace violence, depressive symptoms, psychological capital